Global burden, trends, and disparities in kidney cancer attributable to smoking from 1990 to 2021 - Siyu Han; Shiyu Zhao; Ran Zhong; Peizhe Li; Yuewen Pang; Shuang He; Junyao Duan; Huijie Gong; Jing Shi; Li Liu; Yongji Yan (Frontiers in Public Health)
PurposeSmoking is a well-established risk factor for kidney cancer. Analyzing the latest global spatio-temporal trends in the kidney cancer burden attributable to smoking is critical for informing effective public health policies.MethodsUsing data from the 2021 GBD database, we examined deaths, disability-adjusted life years (DALYs), and age-standardized rate (ASR) of kidney cancer attributable to smoking across global, regional, and national levels. Trends in ASRs were assessed through estimated annual percentage change (EAPC). We conducted a cross-country analysis to evaluate disparities in the kidney cancer burden from 1990 to 2021, with absolute and relative inequalities measured by the slope index of inequality and concentration index, respectively. Correlation analysis was conducted by the Spearman rank order correlation method. Additionally, we projected age-standardized death and DALYs rates up to 2036 using Bayesian age-period-cohort (BAPC) models in R.ResultsGlobally, kidney cancer deaths attributable to smoking increased by 67.64%, from 9,673 in 1990 to 16,216 in 2021. Despite this increase, the age-standardized death rate (ASDR) dropped from 0.25 to 0.19 per 100,000 (EAPC: −0.93). Similarly, the age-standardized disability-adjusted life years rate (ASDALY) decreased from 6.17 to 4.37 per 100,000 (EAPC: −1.15). Geographically, areas with a higher Socio-demographic Index (SDI) were the most affected. The positive correlation between higher SDI and increased deaths highlights the role of economic and social factors in disease prevalence. Cross-country analysis shows that while relative inequalities between groups are improving, absolute differences in health burdens continue to grow. Furthermore, projections indicate a gradual decline in ASDR and ASDALY for both sexes from 2022 to 2036.ConclusionBetween 1990 and 2021, both the global ASDR and ASDALY attributable to smoking in kidney cancer, which are positively correlated with SDI, have declined. However, significant demographic and geographic disparities persist, with the disease burden remaining higher in older populations and regions with elevated SDI levels. Moreover, while the overall burden is projected to decline annually over the next 15 years, it is expected to remain significantly higher in men. These findings emphasize the need for region-specific health prevention strategies to reduce smoking-related kidney cancer.